Correlation of Pelvic Magnetic Resonance Imaging Diagnosis With Pathology for Indeterminate Adnexal Masses. Issue 7 (1st September 2014) - Haggerty, Ashley F.; Hagemann, Andrea R.; Chu, Christina; Siegelman, Evan S.; Rubin, Stephen C.
Abstract : Objectives: The aim of this study was to determine the accuracy of pelvic magnetic resonance imaging (MRI) diagnoses compared with the final pathology diagnoses for a series of women with indeterminate adnexal masses. Materials and Methods: We performed a retrospective cohort study of women who underwent pelvic MRI with a diagnosis of an adnexal mass between June 2009 and 2010 after indeterminate ultrasound at our tertiary care institution. Chart abstraction was performed for demographic information and radiologic interpretations (benign or malignant) and favored a specific histologic subtype on MRI reports. The radiologic diagnoses were compared with the diagnoses by surgical pathology. Results: Data from 237 female patients who underwent pelvic MRI were included, and 41.35% underwent surgical intervention for the adnexal mass. Pelvic MRI (n = 88) was determined to have a sensitivity of 95.0% and specificity of 94.1%. The predicted specific histologic subtype by MRI (n = 84) was accurate in 56 (98.25%) of 57 women with an anticipated benign diagnosis and in 23 (85.19%) of 27 women with an anticipated malignancy. The agreement between a benign diagnosis from MRI and benign final surgical pathology was 0.85 (95% confidence interval, 0.716–0.976). Conclusions: In our tertiary care center, MRI is used to further characterize indeterminate adnexal masses and can accurately differentiate benign versus malignant adnexal masses. The diagnosis on MRI was highly correlative with the final histopathology. The majority of the cohort (59%) were able to be managed expectantly based on reassuring results of the MRI. Magnetic resonance imaging offered diagnostic value, more detailed patient counseling, appropriate subspecialty referral, and surgical planning, as well as reassurance to pursue conservative management of benign masses by MRI.